2021
DOI: 10.2141/jpsa.0200016
|View full text |Cite
|
Sign up to set email alerts
|

<i>Ex Ovo</i> Culture System for Avian Embryos and its Application

Abstract: Ex ovo culture of avian embryos can be applied not only to embryology but also to various fields of basic research such as embryo manipulation, toxicology, and regenerative medicine. The windowing method, which facilitates various manipulations and observations by opening a hole in one part of the eggshell, and culture systems using surrogate eggshells, are widely used. Despite this, biology lessons in high schools cover shell-less culture systems, which involve the development of avian embryos in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…On the other hand, the water content of egg white decreased from 90% to about 60%, resulting in thicker egg white. The same phenomenon was observed by Ex Ovo Culture System [7]. Furthermore, by analyzing the SDS-PAGE and Western blotting profiles of the egg yolk in fertilized eggs, OVA was significantly detected by immunostaining from the watery egg yolk on day 2-7.…”
Section: Quantitative and Qualitative Changes In Egg Constituents During Incubationsupporting
confidence: 74%
“…On the other hand, the water content of egg white decreased from 90% to about 60%, resulting in thicker egg white. The same phenomenon was observed by Ex Ovo Culture System [7]. Furthermore, by analyzing the SDS-PAGE and Western blotting profiles of the egg yolk in fertilized eggs, OVA was significantly detected by immunostaining from the watery egg yolk on day 2-7.…”
Section: Quantitative and Qualitative Changes In Egg Constituents During Incubationsupporting
confidence: 74%
“…In this system, embryo development is observed from the top of the culture system; however, the vascular system that develops along the side of the culture system is not visible. More recently, the successful hatching of normal chicks from cSLCS, which uses transparent polymethylpentene wrap, has been reported (Tahara and Obara 2014;Tahara and Obara 2021). Even though the hatchability of the cSLCS remains low, it may be used to continuously monitor the phenotypic outcome of experimental treatments from any direction throughout the incubation period until hatching.…”
Section: Shell-less Culture Of Avian Embryosmentioning
confidence: 99%
“…Furthermore, calcium from the eggshells is also needed for ossification, and its deficit results in limb deformity ( Cloney and Franz-Odendaal, 2015 ); therefore, supplying calcium to developing embryos is required ( Elliott and Bennett, 1971 ; Rowlett and Simkiss, 1987 ). During the ex ovo culture, the embryos develop with no eggshells as the protective structure leading to a high mortality rate ( Tahara and Obara, 2021 ). Therefore, adding calcium carbonate to the CAM in shell-less cultured embryos helped to increase more than 40% hatchability ( Tahara et al, 2021 ).…”
Section: Ex Ovo Cultivation Of Avian Embryos: Environmental ...mentioning
confidence: 99%
“… Tahara and Obara (2014) demonstrated that these materials should possess oxygen permeability. One important point that also increases viability and hatchability is smoothening of film surface since film wrinkles caused a low survival rate of culture embryos ( Tahara and Obara, 2014 , 2021 ). Although using transparent films would help to facilitate whole-embryo observation, some disadvantages of their properties should be ameliorated to increase the hatchability rate.…”
Section: Ex Ovo Cultivation Of Avian Embryos: Environmental ...mentioning
confidence: 99%